Measuring motives for physical activity in adults / Keyvan Molanorouzi - Molanorouzi, Keyvan (2015)
Although there is abundant evidence to recommend a physically active lifestyle, adult physical activity (PA) levels have declined. In order to understand why this happens, studies have been conducted to uncover the reasons for people’s participation in PA. The Physical Activity and Leisure Motivation Scale (PALMS) was created to be a comprehensive tool to measure motives for participating in PA. The present thesis consists of three studies investigating the validation of PALMS in Malaysian adults. In Study 1, I examined the reliability and validity of the PALMS. In Study 2, I investigated the construct validity of the PALMS by testing whether motives for participation best discriminated between types of PA, age, and gender. Finally, in Study 3, I further investigated the construct validity of the PALMS by examining whether PA motives predicted actual amount of PA at a later time. In Study 1, a total of 502 (259 males, 243 females) Malaysian volunteer participants, aged 17 to 67 years completed the PALMS and REMM (questionnaire from which the PALMS was developed). The hypothesized eight sub-scale model demonstrated acceptable fit with the data (CMIN/DF = 2.820, NFI = 0.90, CFI = 0.91, RMSEA = 0.06). Cronbach’s alpha coefficient (α = 0.79) indicated good internal consistency for the overall measure. Internal consistency for the PALMS sub-scales was sound, ranging from 0.78 to 0.82 Spearman’s rho (rs = 0.86, p < 0.001) indicated strong criterion validity with the REMM. The test-retest reliability for the PALMS sub-scales was between 0.78 and 0.94 over a 4-week period. In Study 2, a quantitative, cross-sectional descriptive research design was employed. The PALMS was used to assess motives for PA in 1,360 adults (703 males, 657 females). Respondents were divided into two age groups (young adults aged 20 to 40 years and middle-aged adults 41 to 64 years) and five types of activity (individual sports, team sports, racquet sports, martial arts, and exercise). The group discriminant function analyses revealed significant canonical functions correctly classifying the cases into gender, age group, and type of activities group. The findings in this study suggest that strong and important motives for participation in PA are different across gender, age, and type of activity in adults. In Study 3, a quantitative, cross-sectional descriptive research design was employed. The PALMS was used to assess motives for PA in adults on two occasions. A sample of 493 undergraduate students aged 18 to 25 years took part in the study. The results showed that not only were pertinent sub-scales of PALMS positively related to amount of PA, but separate regression analyses showed the positive predictive effect of PALMS motives for amount of PA for each type of PA among participants. This study supported the construct validity of the PALMS by showing that the motives measured by PALMS did predict amount of PA. The three studies in this thesis signal strong potential for the PALMS to be used in practice to advise individuals about suitable PA based on their primary motives for participating.